Implementasi Kegiatan Ekstrakurikuler Kaligrafi dalam Mengembangkan Kreativitas Peserta Didik di SDIT Yayasan Wakaf Al-Kaffah Binjai - Neliwati; Nur Hidayah; Nadya Arifah Malasari; Juan Adji Rizki (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2023)
The aim of this research is to understand the phenomena experienced by research subjects, for example behavior, perceptions, motivation, actions, etc., holistically, and by means of descriptions in the form of words and language, in a special natural and natural context. by utilizing various natural methods. This research method uses qualitative methods with descriptive research type. Data collection techniques, interview techniques, observation, and document review. The subjects of this research are teachers who handle the calligraphy extracurricular program at the Al-Kaffah Binjai Waqf Foundation. The results of this research show that teachers can develop students' creativity through calligraphy extracurricular activities at the Al-Kaffah Binjai Waqf Foundation using various strategies.